Inglês na palma da mão: letramento crítico e ensino de inglês para alunos surdos - Felipe de Almeida Coura (2016)
This study investigated English classes for deaf students considering the activities done by participants, which involved reading and writing in English, discussions in Brazilian Sign Language (Libras), as well as impressions of the teacher-researcher and the students about the classes. The literature review includes studies on literacy, new literacies, and especially critical literacy. This research also addresses the educational needs of deaf students in Brazil, and linguistic and cultural particularities of this minority group, involving the learning of reading and writing in Portuguese and in a foreign language. The main objective is to understand whether critical literacy can contribute not only to participants reading and writing in English, but also to their gaining of significant increases for a critical attitude in several recurring situations in society. To this end, the methodology used features of case study and classroom research, focusing on action research. The main data collection instruments were classroom video-taping and the activities done by students. The classes were divided into eight units, each of which had a distinct theme, focusing on the promotion of critical literacy. The deaf students were teenagers and young adults between 17 and 21 years old, all of them at a beginner level of English learning, attending the 3rd year of the Youth and Adult Education (which is the last year of elementary school). The research showed that the topics discussed in class, through images, videos and texts in English, were not very explored by other teachers. After the analysis, moments that made possible a greater awareness about socio-political issues were perceived, such as racism and social inclusion. The results also revealed that, even if the classes focused on critical literacy, the teaching of structural features of the language were also present in some moments, evidenced by the concept of autonomous literacy, for example. The contribution of a non-linear educational planning and the advances that interactions in Libras brought to the classes are also important points to be highlighted in this research, because they have contributed to English learning. Finally, an organization of the analysis of the data made from the continua model of biliteracy also brought significant reflections which contributed to a better understanding of the context and the participants in this study.